Relationship between BMI (Body Mass Index) and Cholesterol in the Community Around UPN "Veteran" Jawa Timur - Fara Disa Durry; Prasetyaning Estu Pratiwi; Irma Seliana; Zulfan Febriawan (Jurnal EduHealth, 2023)
Cholesterol is a risk factor for non-communicable diseases. High cholesterol levels that exceed normal limits or hypercholesterolemia can be a risk factor that causes various non-communicable diseases such as an increased risk of hypertension, obesity, stroke and coronary heart disease. The factor associated with high cholesterol is Body Mass Index (BMI). High body mass index (BMI) is caused by high calorie consumption patterns, lack of physical activity, and consuming foods that contain high amounts of calories, salt and fat, including cholesterol. Weight gain is also associated with increased serum cholesterol levels. The aim of this research is to determine the relationship between BMI and cholesterol levels in the community around UPN "Veteran" Jawa Timur. The method used is descriptive-analytic with a cross-sectional research design. The research sample used was the community around UPN "Veteran" Jawa Timur who visited UPN Serving activities. The sample consisted of 69 people with sampling using simple random sampling techniques. Data analysis used bivariate analysis (chi square test). The results showed that of the 69 respondents, the largest percentage of BMI was normal at 52.4%, overweight at 31.9% and obesity 1 at 8.7%. Meanwhile, the results of cholesterol levels were obtained from 29 people in the high cholesterol level category and 40 people in the low cholesterol level category. The Chi-Square test between body mass index (BMI) and cholesterol levels in the community around UPN "Veteran" Jawa Timur obtained a statistical result of 0.675 (p > 0.05). The conclusion of the research is that there is no relationship between body mass index (BMI) and cholesterol levels in the community around UPN "Veteran" Jawa Timur .